HUMAN RESOURCES MANAGEMENT - Buckley M. Ronald; Fedor Donald B; Ferris Gerald R (Prentice Hall, 2002)
THE FIELD OF HRM THE EXTERNAL CONTEXT OF HRM FUNCTIONS OF HRM THE INTERNAL CONTEXT OF HRM OUTCOMES OF HRM
THE FIELD OF HRM THE EXTERNAL CONTEXT OF HRM FUNCTIONS OF HRM THE INTERNAL CONTEXT OF HRM OUTCOMES OF HRM